Teachers’ Stressors, Satisfaction, and Support: An Exploration of Work-Related Factors - Ang-og, Augustin; Naparan, Genesis (Journal of Education and Learning Reviews, 2025)
Background and Aim: The teachers working in elementary schools in the Philippines have encountered various types of stress that cause significant harm to their well-being and satisfaction with their work. The purpose of this research was to identify the personal and professional stress factors experienced by teachers, the coping skills they implemented, their level of job satisfaction, and the support provided by school administration. Materials and methods: A qualitative instrumental case study design was employed to capture the perspectives of 20 purposively selected elementary teachers from both public and private schools. Data were collected through semi-structured interviews using an open-ended guide focused on stress, coping strategies, job satisfaction, and administrative support. Thematic analysis was conducted to generate patterns and insights. Results: Results showed that teachers faced multiple stressors, such as health issues, financial problems, work overload, and student misbehavior. Coping strategies varied, with 65% of participants engaging in wellness activities (e.g., exercise or meditation) and 45% seeking peer support and collaboration. Job satisfaction fluctuated depending on students’ progress and recognition, but decreased with increased administrative duties, low wages, and insufficient educational materials. Although 70% of participants reported receiving emotional or technical support from administrators, most noted that these efforts were insufficient. Conclusion: Personal and institutional factors strongly influence teachers’ well-being and job satisfaction. The analysis highlights the need to increase emotional support, reduce administrative burdens, and improve access to teaching resources by developing supportive policies and programs. School administrators and curriculum designers can use these findings to establish systems that sustain teacher efficiency and engagement, thereby improving student learning outcomes.